The determinants of FDI location choice in China: a discrete-choice analysis. Issue 13 (16th March 2017) - Belkhodja, Omar; Mohiuddin, Muhammad; Karuranga, Egide
ABSTRACT: This study addresses two questions: What are the determinants of foreign direct investment (FDI) location choice in China? What are the factors that determine investors' choice between 'Economic zones' in China on one hand, and 'other cities' of China on the other hand? This study shows that FDI location choice is sensitive both on the endowment conditions in different regions/cities/economic zones in China as well as on the country of origin of the FDI. Based on a data set of 1218 observations, the results of the binary logit regressions indicate that the protection of intellectual rights, agglomeration economies, investments in education and gross regional product affect the location choice of FDI in China. This choices, however, varies depending on the origin of the FDI. Policy makers can use these findings to channel FDI to targeted regions/ cities.